On the importance of (1) a larger infusion of the industrial element into our system of education, and of (2) an adaptation to Ireland of the day industrial clauses of Lord Sandon's act of 1876 - Falkiner, F. R. (Statistical and Social Inquiry Society of Ireland, 1877)
On the 16th March in the present year there was a debate in the House of Commons, of interest to Ireland more deep than pleasant. In a speech admirable for ability and earnest feeling, Mr. O'Shaughnessy, M.P. for Limerick, moved that ?It is expedient to adopt measures, consistent with economy and the rights of conscience, to promote the general diffusion of elementary education amongst the Irish people?. With figures more significant than those of speech he supported his resolution, quoting from the last census these numbers: Children of school age in all Ireland, 1,500,000; of these on the rolls of the national schools, 1,000,000; average attendance of those so enrolled, 389,000, only.
Read before the Society, 24 April 1877
Keywords: Industrial schools; Reformatory schools; Irish education system; 314.15